Analisis Faktor-Faktor yang Mempengaruhi Hubungan Toleransi Beragama Antar Mahasiswa Semester 1 di Universitas Muhammadyah Maumere - Katharina Woli Namang; Nona Lin (PT PUSTAKA CENDEKIA GROUP, 2025)
Tolerance is human behavior to respect and respect differencesin a certain environment or group. The relationship between tolerance towards others is to create an attitude of mutual understanding and it is very important to respect each other. Religious tolerance is tolerance related to the beliefs or belief held by each person that are related to divinity. Religious tolerance is also an attitude to recognize peace and not deviate from recognized and applicable norms.